Pengaruh Nilai Tukar dan Nilai Ekspor Gas Alam Terhadap Penerimaan Pajak Ekspor - Sinar Tiara; Khairul Amri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research aims to analyze the influence of the exchange rate and the value of natural gas exports on Indonesian export tax revenues and analyze the causal relationship between these three variables. Using data in the form of time series data for the period 2005 to 2022 (n = 18). Data were analyzed using Multiple Linear Regression and Vector Error Correction Model (VECM) methods. The results of this research show that in the long term the value of natural gas exports has a positive and significant effect on export tax revenues. Meanwhile, in the short term, export tax revenues in the previous year have a negative and significant effect on the value of natural gas exports in the current year. The results of this research also show that there is a two-way causal relationship between the Natural Gas Export Value and the Exchange Rate. Furthermore, there is a one-way causal relationship between Export Tax Revenues and the Exchange Rate and between Natural Gas Export Values and Export Tax Revenues.